Are the Indian National Highway PPPs More Efficient than Non-PPPs? An Empirical Analysis through Data Envelopment Analysis. (June 2016) - Gopalkrishna, Nagesha; Karnam, Gayithri
Presently, the entire world is moving to adopt Public Private Partnership 1 (PPP) mode as an alternative to the traditional mode 2 of 'item rate of contract' to provide both economic and social infrastructure. This move is due to the professed advantages of PPPs, such as improved efficiency in service delivery, hassle-free operation and maintenance, on-time completion, synergy between the government and concessionaire in optimum distribution of project risks and creation of value for money 3 to all the stakeholders. To empirically verify the higher efficiency argument of PPPs compared to traditional mode, the present article has attempted to estimate various efficiency scores of the 520 national highway (NH) PPP and Non-PPP projects by employing the widely accepted mathematical tool data envelopment analysis. The present study finds from its empirical estimates that mean technical efficiency (TE) (both full and pure TE) and scale efficiency scores of PPPs are higher than the other projects. The study cites the possible reasons for this could be because of superior technical and managerial skills of the private sector, scale efficiencies of the private sector, payment based on assured quality services and their regular availability, optimum project risk distribution between public and private sectors, long-term nature of bundled contract of construction and operation of the project over the entire concession period, etc.